PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA, UTANG LUAR NEGERI DAN KEMISKINAN (KAJIAN TEORITIS DI INDONESIA) - Susilowati, Dwi; Suliswanto, Muhammad Sri Wahyudi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
This study was conducted with the intention of examining the causal relationship between the following variables: Human Development Index (HDI), foreign debt, poverty, and economic growth. The data used in this investigation was secondary data from 1990 to 2013 which then analyzed by applying Granger causality tests performed six times that ultimately obtained the following results: (1) there was no causal relationship between Human Development Index (HDI) and Foreign Debt (AD); (2) there was a one-way causal relationship between foreign debt (AD) and poverty; (3) there was a one-way causal relationship between economic growth with Foreign Debt (AD); (4) there was no causal relationship between poverty with Human Development Index (HDI); (5) there was no causal relationship between Economic Growth and Human Development Index (HDI); and (6) there was a one-way causal relationship between economic growth and poverty.